2016
DOI: 10.1063/1.4954873
|View full text |Cite
|
Sign up to set email alerts
|

The thermal history effect on shear band initiation in metallic glass

Abstract: The effect of thermal history on shear band initiation in metallic glass is investigated with spherical nanoindentation. Our results clearly show that the indentation size effect on the metallic-glass hardness varies systematically with the thermal history, which is in excellent agreement with the softening-induced shear-band initiation model we recently developed. On a fundamental level, the outcome of our research establishes a correlation between the shear modulus and the critical length scale for initiatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…[38][39][40] Our previous work 31 studied the effect of indenter radius on pop-in events, which showed the larger the indenter, the lower the pop-in stress and the higher the variation in the pop-in stress. Because the contact radius at pop-in increases with the increase of indenter radius, …”
Section: -3mentioning
confidence: 99%
“…[38][39][40] Our previous work 31 studied the effect of indenter radius on pop-in events, which showed the larger the indenter, the lower the pop-in stress and the higher the variation in the pop-in stress. Because the contact radius at pop-in increases with the increase of indenter radius, …”
Section: -3mentioning
confidence: 99%
“…It is also found that the typical strength criteria, such as Von-mises and Tresca criteria, are not suitable for understanding the deviation of fracture plane from the maximum shear stress plane8, and the applicability of the Mohr-Coulomb criterion is still controversial for BMGs81516. In the past several decades, many researchers have done a lot of work on the deformation and fracture mechanism for BMGs and all kinds of theories have been proposed316171819202122. For example, the shear transformation zone (STZ) theory317 assumes that a shear-induced atomic rearrangement occurs at local clusters that are a few to hundreds of atoms in size.…”
mentioning
confidence: 99%
“…The free volume theory1819 takes into account the dependence of flow defect concentration on deformation and describes the relationship between the change of free volume and applied shear stress. In addition, some new fracture criteria have been set up to describe the fracture behaviors of BMGs1620, a universal scaling law that demonstrated the intrinsic correlation between yielding and glass-liquid transition were reported for the understanding of strength and deformation of BMGs21, and the effect of thermal history on shear band initiation was investigated for the yield behavior in BMGs22. These new theoretical and experimental progresses have greatly promoted the research of mechanical behaviors for BMGs.…”
mentioning
confidence: 99%